If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-19 + n) = -40 (-19 * 4 + n * 4) = -40 (-76 + 4n) = -40 Solving -76 + 4n = -40 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '76' to each side of the equation. -76 + 76 + 4n = -40 + 76 Combine like terms: -76 + 76 = 0 0 + 4n = -40 + 76 4n = -40 + 76 Combine like terms: -40 + 76 = 36 4n = 36 Divide each side by '4'. n = 9 Simplifying n = 9
| 5n-4=n-8 | | 1.6x+14.2=3.5x-1 | | 14w=6w+40 | | 2+.10(30)=y | | 5+g=2 | | 90+0.25*x=1000-x | | 2+i=4 | | 3a+4a=9 | | 12x^2+12=25 | | 8+11b=-146 | | 3.95+.05(30)=y | | 15x+3-30x+6=2 | | 1.3+5.2=3.1x-2 | | -12(8+v)=36 | | 4(x+10)+5x=9x-40 | | 8j=6 | | 3tan^2(x)-5tan(x)-2=0 | | 90+0.25x=0 | | -38=-28+x | | 4+2x=4(2x+2)-7(x-2) | | -115=5n | | -8+2w=0 | | 32+(5+x)=20 | | 3.95+.05(10)=y | | -10=x+(-20) | | 0-5y=13 | | -8n=-192 | | 3.95+.05(10)= | | -8n=-921 | | 10-3*(4-2)+1=1 | | 4s+s=5 | | 6-5y=13 |